Study Strategies Comparison and Self-Regulationin University Students - Irma Rosa Alvarado Guerrero; Zaira Vega Valero; María Luisa Cepeda Islas; Ana Elena Del Bosque Fuentes (Universidad Autónoma de Baja California, 2014)
The main factors associated with academic performance are study strategies and self-regulation in university students, thus the objective of this paper is to compare two sample groups: those in a regular status and others under certain academic lag. The Study Strategies Inventory and Self-Regulation (IEEA) BY Castaneda was applied to 41 learners. It was observed that both groups need support to develop strategies for the four scales of the instrument: Information acquisition, memory resource management, information processing and self-regulation in all three dimensions: people, tasks and materials. In conclusion there is a need to develop programs to help the consolidation of study strategies and self-regulation and highlights the importance of analyzing the factors in teacher's education and development of programs and curricula, to improve academic performance in higher educationinstitutions.